THE PROBLEM OF THE RELATIONSHIP BETWEEN THEORETICAL AND EMPIRICAL THINKING - Ye. Denysenko (Academy of Cognitive and Natural Sciences, 2010)
The article reveals some aspects of theoretical and empirical thinking and the question of their correlation opens up.